Nature and Consequences of Biological Reductionism for the Immunological Study of Infectious Diseases - Rivas, Ariel L.; Leitner, Gabriel; Jankowski, Mark D.; Hoogesteijn, Almira L.; Iandiorio, Michelle J.; Chatzipanagiotou, Stylianos; Ioannidis, Anastasios; Blum, Shlomo E.; Piccinini, Renata; Antoniades, Athos; Fazio, Jane C.; Apidianakis, Yiorgos; et al. (Frontiers in Immunology, 2017)
Evolution has conserved ‘economic’ systems that perform many functions, faster or better, with less. For example, three to five leukocyte types protect from thousands of pathogens. To achieve so much with so little, biological systems combine their limited elements, creating complex structures. Yet, the prevalent research paradigm is reductionist. Focusing on infectious diseases, reductionist and non-reductionist views are here described. The literature indicates that reductionism is associated with information loss and errors, while non-reductionist operations can extract more information from the same data. When designed to capture one-to-many/many-to-one interactions –including the use of arrows that connect pairs of consecutive observations–, non-reductionist (spatial-temporal) constructs eliminate data variability from all dimensions, except along one line, while arrows describe the directionality of temporal changes that occur along the line. To validate the patterns detected by non-reductionist operations, reductionist procedures are needed. Integrated (non-reductionist and reductionist) methods can (i) distinguish data subsets that differ immunologically and statistically; (ii) differentiate false-negative from -positive errors; (iii) discriminate disease stages; (iv) capture in vivo, multilevel interactions that consider the patient, the microbe, and antibiotic-mediated responses; and (v) assess dynamics. Integrated methods provide repeatable and biologically interpretable information.